Polishing composition, polishing method, and method for producing semiconductor substrate

JP7638756B2Active Publication Date: 2025-03-04FUJIMI INCORPORATED
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021057504
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-30
Publication Date
2025-03-04
Estimated Expiration
2041-03-30

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、ポリシリコンおよび窒化ケイ素を含む研磨対象物の研磨において、研磨残りおよびディッシングの両方を抑制できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007638756000006
    Figure 0007638756000006
  • Figure 0007638756000007
    Figure 0007638756000007
  • Figure 0007638756000001
    Figure 0007638756000001
Patent Text Reader

Abstract

To provide means for suppressing part of a polishing target from being left unpolished and the occurrence of dishing in polishing the target including polycrystalline silicon and silicon nitride.SOLUTION: A polishing composition comprises: abrasive grains; ammonia; and at least one potassium compound selected from a group consisting of potassium hydroxide and a potassium salt. In the polishing composition, a content of the ammonia is 0.002 mass% or more and 0.5 mass% or less to a total mass of the polishing composition, and a content of the potassium compound is 0.004 mass% or more and 0.5 mass% or less to the total mass of the polishing composition.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polishing composition, a polishing method, and a method for producing a semiconductor substrate. [Background technology]

[0002] In recent years, new microfabrication technologies have been developed to accompany the high integration and high performance of LSI (Large Scale Integration). Chemical mechanical polishing (CMP) is one of these technologies, and is frequently used in the LSI manufacturing process, especially in the multi-layer wiring formation process, for planarizing interlayer insulating films, forming metal plugs, and forming buried wiring (damascene wiring).

[0003] CMP has been applied to various processes in semiconductor manufacturing, and one example of such application is the gate formation process in transistor fabrication. When fabricating a transistor, Si-containing materials such as silicon, silicon oxide film (silicon oxide), polycrystalline silicon (polysilicon), and silicon nitride (silicon nitride) may be polished, and depending on the transistor structure, it is necessary to control the polishing rate of each Si-containing material.

[0004] For example, Patent Document 1 discloses a chemical mechanical polishing slurry for polishing polycrystalline silicon films, which contains (a) a metal oxide, (b) a quaternary ammonium base, and (c) a fluorosurfactant having a specific structure. Patent Document 1 claims that the use of the slurry can solve the dishing problem and improve in-plane uniformity. Dishing refers to the phenomenon in which the center of the film is recessed into a dish shape. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2009-515335 A Summary of the Invention [Problem to be solved by the invention]

[0006] Recently, there has been an increased demand for polishing objects that include polysilicon and silicon nitride, for example polishing polysilicon to expose silicon nitride.

[0007] However, when such an object is polished using the technique of Patent Document 1, it has been found that polishing residue of polysilicon may be left on the surface of the silicon nitride.

[0008] Therefore, an object of the present invention is to provide a means capable of suppressing both polishing residue and dishing in polishing an object including polysilicon and silicon nitride. [Means for solving the problem]

[0009] In order to solve the above problems, the present inventors have conducted extensive research and have found that the above problems can be solved by controlling the ammonia content and the potassium compound content within specific ranges in a polishing composition containing abrasive grains, ammonia, and a specific potassium compound, and have completed the present invention.

[0010] That is, a polishing composition according to one embodiment of the present invention contains abrasive grains, ammonia, and at least one potassium compound selected from the group consisting of potassium hydroxide and potassium salts, and is characterized in that the content of the ammonia is 0.002% by mass or more and 0.5% by mass or less with respect to the total mass of the polishing composition, and the content of the potassium compound is 0.004% by mass or more and 0.5% by mass or less with respect to the total mass of the polishing composition. Effect of the Invention

[0011] According to the present invention, it is possible to suppress both polishing residue and dishing in polishing an object containing polysilicon and silicon nitride. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is a diagram showing confetti-shaped abrasive grains in one embodiment of the present invention. [Diagram 2] FIG. 1 is a cross-sectional view that illustrates a polishing target (a silicon wafer having a poly-Si pattern formed on its surface) used in the evaluation of polishing residue and dishing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention relates to a polishing composition comprising an abrasive grain, ammonia, and at least one potassium compound selected from the group consisting of potassium hydroxide and potassium salts. The content of the ammonia is 0.002% by mass or more and 0.5% by mass or less with respect to the total mass of the polishing composition, and the content of the potassium compound is 0.004% by mass or more and 0.5% by mass or less with respect to the total mass of the polishing composition. The polishing composition of the present invention having such a configuration can suppress both polishing residue and dishing in polishing an object containing polysilicon (polycrystalline silicon) and silicon nitride. More specifically, when a polysilicon film formed so as to cover the silicon nitride film is polished to the surface of the silicon nitride film, it is possible to suppress the occurrence of polishing residue of polysilicon on the surface of the silicon nitride film while suppressing dishing of the polysilicon film (the amount of dishing can be reduced). In addition, the polishing composition of the present invention can sufficiently increase the polishing rate of polysilicon, but the polishing rate of silicon nitride remains low. As a result, the effect of achieving a sufficiently high ratio of the polishing rate of polysilicon to the polishing rate of silicon nitride (high selectivity) can be obtained.

[0014] The mechanism by which the above-mentioned effects are obtained is believed to be as follows: However, the following mechanism is merely speculation, and the scope of the present invention is not limited thereto.

[0015] Ammonia has the function of extending the bond distance of the Si-Si bond of polysilicon due to the nucleophilic action of the unshared electron pair present in the nitrogen atom. Therefore, if the amount of ammonia is more than a specific amount, the Si-Si bond becomes brittle and the polishing of polysilicon progresses easily. For the same reason, polishing residue of polysilicon is easily removed. On the other hand, if the content of ammonia is high, the above action becomes too large, and dishing is likely to occur (the amount of dishing increases).

[0016] The potassium compound removes the oxide film present on the surface of polysilicon before polishing. If the content of the potassium compound is low, it takes a long time to remove the oxide film, and the polishing of polysilicon is likely to be uneven. As a result, this unevenness can become a polishing residue. On the other hand, if the content of the potassium compound is high, the electrostatic repulsive force between the abrasive grains and the silicon nitride substrate decreases, so that the polishing speed of silicon nitride increases, and the ratio of the polishing speed of polysilicon to the polishing speed of silicon nitride can decrease.

[0017] When the polishing composition contains a water-soluble polymer, the water-soluble polymer functions as a protective film for polysilicon and can suppress the polishing of polysilicon. Therefore, the polishing composition containing a water-soluble polymer is likely to cause the problem of polishing residue of polysilicon. The electrical force with which the ammonia in the polishing composition interacts with the substrate is greater than the electrical force with which the water-soluble polymer interacts with the substrate. Therefore, it is considered that ammonia is more likely to adsorb to the substrate than the water-soluble polymer, and exhibits the effect of making the water-soluble polymer easier to peel off from the polysilicon. In addition, the same mechanism is considered when the potassium compound in the polishing composition is a specific amount or more. That is, the electrical force with which the potassium compound interacts with the substrate is greater than the electrical force with which the water-soluble polymer interacts with the substrate, so it is considered that the potassium compound is more likely to adsorb to the substrate than the water-soluble polymer, and exhibits the effect of making the water-soluble polymer easier to peel off from the polysilicon. Therefore, when the polishing composition contains ammonia and a specific amount or more of a potassium compound, the scraping of the water-soluble polymer by the abrasive grains proceeds more easily, and the polishing of polysilicon is promoted, resulting in less polishing residue.

[0018] Hereinafter, embodiments of the present invention will be described. Note that the present invention is not limited to the following embodiments.

[0019] In this specification, unless otherwise specified, operations and measurements of physical properties are performed under conditions of room temperature (20° C. or higher and 25° C. or lower) and relative humidity of 40% RH or higher and 50% RH or lower.

[0020] In addition, in this specification, "(meth)acrylic" is meant to collectively refer to acrylic and methacrylic, and "(meth)acrylate" is meant to collectively refer to acrylate and methacrylate.

[0021] [Polished object] As described above, the polishing composition according to the present invention can suppress both polishing residue and dishing in polishing an object containing polysilicon and silicon nitride. In addition, as described above, when the polishing composition according to the present invention is applied to an object containing polysilicon and silicon nitride, the ratio of the polishing rate of polysilicon to the polishing rate of silicon nitride is sufficiently high (high selectivity). Therefore, it is preferable that the object to be polished according to the present invention contains polysilicon and silicon nitride. Therefore, according to a preferred embodiment of the present invention, the polishing composition is used to polish an object to be polished containing polysilicon and silicon nitride. According to another preferred embodiment of the present invention, the polishing composition is used for selective polishing of polysilicon relative to silicon nitride.

[0022] The object to be polished according to the present invention may include materials other than polysilicon and silicon nitride, such as silicon carbonitride (SiCN), silicon oxide, metal, and SiGe.

[0023] Examples of objects to be polished that contain silicon oxide include a TEOS-type silicon oxide (hereinafter, also simply referred to as "TEOS-SiO") film produced using tetraethyl orthosilicate as a precursor, a high density plasma (HDP) film, an undoped silicate glass (USG) film, a phosphorus silicate glass (PSG) film, a boron-phosphorus silicate glass (BPSG) film, and a rapid thermal oxidation (RTO) film.

[0024] Examples of the metal include tungsten, copper, aluminum, cobalt, hafnium, nickel, gold, silver, platinum, palladium, rhodium, ruthenium, iridium, and osmium.

[0025] [Abrasive grain] The abrasive grains contained in the polishing composition of the present invention have the effect of mechanically polishing an object to be polished, and improve the polishing rate of the object to be polished by the polishing composition.

[0026] In the polishing composition of the present invention, the abrasive grains are not particularly limited. The types of abrasive grains include particles made of metal oxides such as silica, alumina, zirconia, and titania. The abrasive grains may be used alone or in combination of two or more kinds. The abrasive grains may be commercially available products or synthetic products. Among these abrasive grains, silica is preferred, fumed silica and colloidal silica are more preferred, and colloidal silica is even more preferred. Thus, according to a preferred embodiment of the present invention, the abrasive grains include silica (silica particles). In a more preferred embodiment, the abrasive grains include colloidal silica (colloidal silica particles).

[0027] The colloidal silica can be produced by a method such as a sodium silicate method or a sol-gel method, and any method for producing the colloidal silica can be suitably used as the abrasive grains according to the present embodiment. Among them, the colloidal silica produced by the sol-gel method, which can produce the colloidal silica with high purity, is preferred.

[0028] The shape of the abrasive grains according to the present invention is not particularly limited, and may be spherical or non-spherical. Specific examples of non-spherical shapes include polygonal prisms such as triangular prisms and square prisms, cylinders, bales in which the center of the cylinder is bulging out more than the ends, donuts in which the center of the disk is penetrated, plates, so-called cocoon shapes with a constriction in the center, so-called association-type spheres in which multiple particles are integrated, so-called confetti shapes with multiple protrusions on the surface, and rugby ball shapes, and are not particularly limited. Among them, the shape of the abrasive grains is preferably confetti-shaped. When the shape of the abrasive grains is confetti-shaped, the polishing speed for polysilicon is improved compared to the case where abrasive grains with a smooth surface are used. As a result, polishing residue can be further suppressed. In addition, since the polishing speed for silicon nitride does not change significantly at this time, the ratio of the polishing speed for polysilicon to the polishing speed for silicon nitride can be further improved (high selectivity). Therefore, according to a preferred embodiment of the present invention, the shape of the abrasive grains is confetti-shaped.

[0029] In this specification, the term "confetti-shaped" refers to a particle having multiple protrusions on its surface. In one or more embodiments, the confetti-shaped abrasive grains are formed by agglomeration or fusion of two or more particles whose particle diameters differ by five times or more based on the particle diameter of the smallest particle. Preferably, the smaller particle of the two or more particles whose particle diameters differ by five times or more is partially buried in the larger particle.

[0030] The number of protrusions on the surface of the confetti-shaped abrasive grains is preferably 3 or more, and more preferably 5 or more, on average per grain.

[0031] The protrusions referred to here have a height and width sufficiently smaller than the particle diameter of the confetti-shaped abrasive grains. More specifically, the length of the portion shown as the curve AB passing through points A and B in FIG. 1 does not exceed a quarter of the circumference of the maximum inscribed circle of the confetti-shaped abrasive grains, or more precisely, the circumference of the maximum circle inscribed in the projected outline of the confetti-shaped abrasive grains. The width of the protrusion refers to the width at the base of the protrusion, and is represented in FIG. 1 as the distance between points A and B. The height of the protrusion refers to the distance between the base of the protrusion and the part of the protrusion farthest from the base, and is represented in FIG. 1 as the length of the line segment CD perpendicular to the line AB.

[0032] The average value (protrusion height / protrusion width) obtained by dividing the height of the protrusions on the surface of the confetti-shaped abrasive grains by the width at the base of each of the same protrusions is preferably 0.17 or more, more preferably 0.20 or more, and even more preferably 0.22 or more. As this average value increases, the polishing rate (particularly the polishing rate of polysilicon) with the polishing composition increases because the shape of the protrusions is relatively sharp.

[0033] The average height of the projections on the surface of the confetti-shaped abrasive grains is preferably 3.5 nm or more, more preferably 4.0 nm or more. As the average height of the projections increases, the polishing rate (particularly the polishing rate of polysilicon) with the polishing composition increases.

[0034] The shape (outer shape) of the abrasive grains can be confirmed by a scanning electron microscope. The "average protrusion height" and "average (protrusion height / protrusion width)" are values ​​measured by the method described in the Examples.

[0035] Those skilled in the art can easily manufacture confetti-shaped abrasive grains by appropriately referring to known methods. A preferred embodiment of the manufacturing method for confetti-shaped abrasive grains will be briefly described below. Note that the manufacturing method will be described below using confetti-shaped colloidal silica, which is an example of confetti-shaped silica particles. Note that, in addition to confetti-shaped colloidal silica, confetti-shaped fumed silica can be used as confetti-shaped silica particles. Confetti-shaped colloidal silica is preferred from the viewpoint of suppressing the occurrence of polishing scratches.

[0036] First, a slurry containing colloidal silica particles is obtained by continuously adding alkoxysilane to a mixed solution of methanol and water to which aqueous ammonia is added as a catalyst and hydrolyzing the mixture. The obtained slurry is heated to distill off methanol and ammonia. Then, an organic alkali is added to the slurry as a catalyst, and alkoxysilane is continuously added again at a temperature of 70°C or higher to hydrolyze the mixture, thereby forming multiple protrusions on the surface of the colloidal silica particles. Specific examples of organic alkali that can be used here include amine compounds such as triethanolamine and quaternary ammonium compounds such as tetramethylammonium hydroxide. According to this method, silica particles having multiple protrusions on the surface with a metal impurity content of 1 mass ppm or less can be easily obtained.

[0037] A general method for producing colloidal silica by hydrolysis of alkoxysilane is described, for example, in "Science of the Sol-Gel Method" by Sakuka Sumio (published by Agne Shofusha) on pages 154-156. In addition, JP-A-11-60232 discloses a method for producing cocoon-shaped colloidal silica, in which methyl silicate or a mixture of methyl silicate and methanol is dropped into a mixed solvent consisting of water, methanol, and ammonia or ammonia and an ammonium salt to react with methyl silicate and water. JP-A-2001-48520 discloses a method for producing elongated colloidal silica, in which alkyl silicate is hydrolyzed with an acid catalyst, and then an alkali catalyst is added and heated to promote polymerization of silicic acid to grow particles. JP-A-2007-153732 describes a method for producing colloidal silica having a large number of small protrusions by using a specific type of hydrolysis catalyst in a specific amount and using an easily hydrolyzable organosilicate as a raw material. JP 2002-338232 A describes a method for producing secondary aggregated colloidal silica by adding an aggregating agent to monodispersed colloidal silica to secondary aggregate it into a spherical shape. JP 07-118008 A and WO 2007 / 018069 A disclose the addition of calcium salt or magnesium salt to active silicic acid obtained from sodium silicate in order to obtain colloidal silica of irregular shape such as elongated shape. JP 2001-11433 A describes the addition of calcium salt to active silicic acid obtained from sodium silicate to obtain beaded colloidal silica. JP 2008-169102 A describes the generation and growth of microparticles on the surface of seed particles to obtain colloidal silica having many small protrusions like confetti. The confetti-shaped silica particles according to the present invention can be produced by using the methods described in these documents alone or in combination.

[0038] The abrasive grains according to the present invention are preferably one having a lower silanol group density (fewer silanol groups per unit surface area). When the silanol group density is low, the amount of bound water present between the abrasive grains and the polysilicon surface is reduced. This makes it easier for the abrasive grains to come into contact with the polysilicon surface, and the polishing speed of the polysilicon can be further improved. As a result, polishing residue can be further suppressed. In addition, since the polishing speed for silicon nitride does not change significantly at this time, the ratio of the polishing speed for polysilicon to the polishing speed for silicon nitride can be further improved (high selectivity). Specifically, the silanol group density of the abrasive grains is 0 particles / nm 2 More than 4 pieces / nm 2 Therefore, according to a preferred embodiment of the present invention, the silanol group density of the abrasive grains is 0 / nm 2 More than 4 pieces / nm 2 The lower the silanol group density, the better, so the lower the silanol group density is, 3.8 / nm 2 Below, 3.7 pieces / nm 2 Below, 3.6 pieces / nm 2 Below, 3.5 pieces / nm 2 The following order of preference is given. Note that the lower limit of the silanol group density is preferably 0 / nm 2 However, if the abrasive grains contain silica (silica particles), a certain amount of silanol groups may be contained. Therefore, the lower limit of the silanol group density is 0.5 / nm 2 More than 1.0 pieces / nm 2 More than 1.5 pieces / nm 2 More than 2.0 pieces / nm 2 Therefore, the silanol group density is preferably 0.5 / nm 2 More than 3.8 pieces / nm 2 More preferably, it is 1.0 particles / nm 2 More than 3.7 pieces / nm 2 More preferably, it is 1.5 particles / nm 2 More than 3.6 pieces / nm 2 or less, and particularly preferably 2.0 particles / nm 2 More than 3.5 pieces / nm 2The silanol group density can be reduced by carrying out a heat treatment such as calcination in the manufacturing method of the abrasive grains. In this specification, the silanol group density is a value measured by the method described in the Examples.

[0039] Furthermore, the abrasive grains may be surface-modified as long as the silanol group density satisfies the above range. Among them, colloidal silica with an organic acid immobilized thereon is particularly preferred. The immobilization of the organic acid on the surface of colloidal silica contained in the polishing composition is achieved, for example, by chemically bonding the functional group of the organic acid to the surface of the colloidal silica. The immobilization of the organic acid on the colloidal silica is not achieved by simply allowing colloidal silica and an organic acid to coexist. If sulfonic acid, which is a type of organic acid, is to be immobilized on colloidal silica, it can be achieved, for example, by the method described in “Sulfonic acid-functionalized silica through quantitative oxidation of thiol groups”, Chem. Commun. 246-247 (2003). Specifically, a silane coupling agent having a thiol group, such as 3-mercaptopropyltrimethoxysilane, is coupled to colloidal silica, and then the thiol group is oxidized with hydrogen peroxide, thereby obtaining colloidal silica with a sulfonic acid immobilized on the surface. Alternatively, when a carboxylic acid is immobilized on colloidal silica, it can be carried out by, for example, the method described in “Novel Silane Coupling Agents Containing a Photolabile 2-Nitrobenzyl Ester for Introduction of a Carboxy Group on the Surface of Silica Gel”, Chemistry Letters, 3, 228-229 (2000). Specifically, a silane coupling agent containing a photoreactive 2-nitrobenzyl ester is coupled to colloidal silica, and then the resulting mixture is irradiated with light to obtain colloidal silica having a carboxylic acid immobilized on the surface.

[0040] The abrasive grains according to the present invention are preferably as high as possible in true density. With a high true density, mechanical force can be efficiently transmitted to the wafer, and as a result, polishing residue can be further suppressed. In addition, since the polishing speed for silicon nitride does not change significantly, the ratio of the polishing speed for polysilicon to the polishing speed for silicon nitride can be further improved (high selectivity). Specifically, the true density is 1.9 g / cm 3 Thus, according to a preferred embodiment of the present invention, the true density of the abrasive grains is 1.9 g / cm 3 That's all. The higher the true density, the better, so 2.0 g / cm 3 More preferably, 2.05 g / cm 3 The upper limit is not particularly limited, but is usually 3.0 g / cm. 3 Less than or equal to 2.5 g / cm 3 Less than 2.2 g / cm is preferred. 3 Therefore, the true density is preferably in the range of 1.9 g / cm or less. 3 More than 3.0g / cm 3 More preferably, it is 2.0 g / cm 3 More than 2.5g / cm 3 More preferably, it is 2.05 g / cm or less. 3 More than 2.2g / cm 3 The true density can be controlled by reducing the porosity by adjusting the reaction temperature and reaction time in the manufacturing method of the abrasive grains (sol-gel method). In this specification, the true density is a value measured by the method described in the Examples.

[0041] The size of the abrasive grains is not particularly limited. For example, the average primary particle diameter of the abrasive grains is preferably 10 nm or more, more preferably 15 nm or more, and even more preferably 20 nm or more. As the average primary particle diameter of the abrasive grains increases, the polishing speed of the object to be polished by the polishing composition (particularly, the polishing speed of polysilicon) increases. In addition, the average primary particle diameter of the abrasive grains is preferably 300 nm or less, more preferably 100 nm or less, even more preferably 50 nm or less, and particularly preferably 30 nm or less. As the average primary particle diameter of the abrasive grains decreases, it becomes easier to obtain a surface with fewer defects by polishing with the polishing composition. That is, the average primary particle diameter of the abrasive grains is preferably 10 nm or more and 300 nm or less, more preferably 15 nm or more and 100 nm or less, even more preferably 20 nm or more and 50 nm or less, and particularly preferably 20 nm or more and 30 nm or less. The average primary particle diameter of the abrasive grains can be calculated, for example, based on the specific surface area (SA) of the abrasive grains calculated by the BET method, assuming that the shape of the abrasive grains is a true sphere. In this specification, the average primary particle size of the abrasive grains is a value measured by the method described in the Examples.

[0042] In addition, the average secondary particle diameter of the abrasive grains is preferably 20 nm or more, more preferably 30 nm or more, and even more preferably 35 nm or more. As the average secondary particle diameter of the abrasive grains increases, the resistance during polishing decreases, enabling stable polishing. In addition, the average secondary particle diameter of the abrasive grains is preferably 400 nm or less, more preferably 250 nm or less, even more preferably 100 nm or less, and particularly preferably 70 nm or less. As the average secondary particle diameter of the abrasive grains decreases, the surface area per unit mass of the abrasive grains increases, the contact frequency with the object to be polished increases, and the polishing speed (particularly the polishing speed of polysilicon) increases. That is, the average secondary particle diameter of the abrasive grains is preferably 20 nm or more and 400 nm or less, more preferably 30 nm or more and 250 nm or less, even more preferably 35 nm or more and 100 nm or less, and particularly preferably 35 nm or more and 70 nm or less. In addition, when the shape of the abrasive grains is confetti-shaped, the secondary particles referred to here refer to particles formed by the association of the confetti-shaped abrasive grains in the polishing composition. The average secondary particle size of the abrasive grains can be measured, for example, by a dynamic light scattering method. In this specification, the average secondary particle size of the abrasive grains is a value measured by the method described in the Examples.

[0043] In the polishing composition according to the present invention, the content (concentration) of the abrasive grains is not particularly limited, but is preferably 0.1 mass% or more, more preferably 0.2 mass% or more, even more preferably 0.5 mass% or more, and particularly preferably more than 0.5 mass% based on the total mass of the polishing composition. The upper limit of the content of the abrasive grains is preferably 20 mass% or less, more preferably 10 mass% or less, even more preferably 5 mass% or less, and particularly preferably less than 5 mass% based on the total mass of the polishing composition. That is, the content of the abrasive grains is preferably 0.1 mass% or more and 20 mass% or less, more preferably 0.2 mass% or more and 10 mass% or less, even more preferably 0.5 mass% or more and 5 mass% or less, and particularly preferably more than 0.5 mass% and less than 5 mass% based on the total mass of the polishing composition. Within such a range, the balance between the polishing rate of polysilicon and the polishing rate of silicon nitride can be further improved while suppressing costs. Therefore, the ratio (selectivity) of the polishing rate of polysilicon to the polishing rate of silicon nitride can be further improved. When the polishing composition contains two or more types of abrasive grains, the content of the abrasive grains refers to the total amount of these.

[0044] [ammonia] The ammonia contained in the polishing composition of the present invention has the effect of promoting the polishing of polysilicon. This is believed to be because the nucleophilic action of the unshared electron pair of ammonia embrittles the Si-Si bond of polysilicon, facilitating the polishing by the abrasive grains.

[0045] In the polishing composition according to the present invention, the content (concentration) of ammonia is 0.002% by mass or more and 0.5% by mass or less with respect to the total mass of the polishing composition. If the content of ammonia is less than 0.002% by mass, the above-mentioned effect of promoting polishing of polysilicon is not fully exhibited. As a result, the problem of the present invention of suppressing polishing residue may not be solved. On the other hand, if the content of ammonia exceeds 0.5% by mass, the above-mentioned effect of promoting polishing of polysilicon becomes too large. As a result, the problem of the present invention of suppressing dishing may not be solved. From the same viewpoint, the content of ammonia is preferably 0.004% by mass or more and 0.2% by mass or less, more preferably 0.008% by mass or more and 0.14% by mass or less, even more preferably 0.01% by mass or more and 0.1% by mass or less, and particularly preferably 0.014% by mass or more and 0.05% by mass or less.

[0046] [Potassium compounds] The polishing composition of the present invention contains at least one potassium compound selected from the group consisting of potassium hydroxide and potassium salts. The potassium compound in the polishing composition has the effect of removing an oxide film present on the surface of polysilicon before polishing.

[0047] The potassium salt is not particularly limited, and can be appropriately selected from inorganic salts of potassium and organic salts of potassium. Examples of inorganic salts of potassium include potassium chloride, potassium bromide, potassium iodide, potassium carbonate, potassium hydrogen carbonate, potassium nitrate, potassium sulfate, potassium hydrogen sulfate, potassium perchlorate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, potassium phosphate, potassium pyrophosphate, potassium etidronate, etc. Examples of organic salts of potassium include potassium acetate, potassium propionate, potassium citrate, etc.

[0048] Among the potassium compounds, from the viewpoint of improving the selectivity, potassium hydroxide, potassium carbonate, potassium hydrogen carbonate, dipotassium hydrogen phosphate, and potassium phosphate are preferred, and potassium hydroxide, potassium carbonate, and potassium hydrogen carbonate are more preferred.

[0049] These potassium compounds may be used alone or in combination of two or more.

[0050] In the polishing composition according to the present invention, the content (concentration) of the potassium compound is 0.004% by mass or more and 0.5% by mass or less with respect to the total mass of the polishing composition. If the content of the potassium compound is less than 0.004% by mass, it takes a long time to remove the oxide film, and unevenness is likely to occur in the polishing of polysilicon. As a result, this unevenness becomes polishing residue, and there is a risk that the problem of the present invention of suppressing polishing residue will not be solved. On the other hand, if the content of the potassium compound exceeds 0.5% by mass, the electrostatic repulsive force between the abrasive grains and the silicon nitride substrate decreases, so that the polishing rate of silicon nitride increases, and the ratio (selectivity) of the polishing rate of polysilicon to the polishing rate of silicon nitride may decrease. From the same viewpoint, the content of the potassium compound is preferably 0.005% by mass or more and 0.4% by mass or less, more preferably 0.025% by mass or more and 0.3% by mass or less, and even more preferably 0.1% by mass or more and 0.2% by mass or less. In addition, when the polishing composition contains two or more kinds of potassium compounds, the content of the potassium compound means the total amount of these.

[0051] The ratio of the content of the potassium compound to the content of ammonia in the polishing composition of the present invention (potassium compound / ammonia (mass ratio)) is preferably 0.1 to 100, more preferably 0.3 to 70, even more preferably 1 to 30, and particularly preferably 10 to 20. When the ratio is within the above range, a good balance is achieved between improving the polishing rate of polysilicon and reducing the polishing residue. Thus, according to a preferred embodiment of the present invention, the ratio of the content of the potassium compound to the content of ammonia (potassium compound / ammonia (mass ratio)) is 0.1 to 100.

[0052] [Water-soluble polymer] The polishing composition of the present invention may contain a water-soluble polymer as necessary. The water-soluble polymer adheres to the surface of the object to be polished and protects the surface of the object to be polished from uneven or excessive etching. This can improve the surface quality after polishing. Therefore, according to a preferred embodiment of the present invention, the polishing composition further contains a water-soluble polymer.

[0053] In this specification, "water-soluble" means that the solubility in water (25°C) is 1 g / 100 mL or more, and "polymer" means a (co)polymer having a weight-average molecular weight of 1,000 or more. The weight-average molecular weight can be measured by gel permeation chromatography (GPC), and specifically, the value measured by the following measurement method is used.

[0054] (GPC measurement conditions) Measuring device: HLC-8320GPC (Tosoh) Sample concentration: 0.01% by mass Column: TSKgel GMPWXL Detector: Differential refractometer Eluent: 10mM lithium bromide / N,N-dimethylformamide Flow rate: 1mL / min Measurement temperature: 40℃ Molecular weight conversion: Polyethylene glycol conversion Sample injection volume: 200 μL.

[0055] In addition, only when it is not possible to measure by GPC, the molecular weight calculated from the molecular formula is adopted as the weight average molecular weight.

[0056] The water-soluble polymer according to the present invention is not particularly limited, but preferably has a nitrogen atom, more preferably has an amide group, and even more preferably has a lactam structure (cyclic amide structure). When such a water-soluble polymer is used, the formation of a protective film on the surface of the object to be polished is facilitated. Thus, according to a preferred embodiment of the present invention, the water-soluble polymer has a nitrogen atom. According to a more preferred embodiment of the present invention, the water-soluble polymer has an amide group. According to a further preferred embodiment of the present invention, the water-soluble polymer has a lactam structure.

[0057] When the water-soluble polymer has a nitrogen atom (preferably an amide group, more preferably a lactam structure), the water-soluble polymer may contain structural units derived from a monomer having a nitrogen atom (preferably an amide group, more preferably a lactam structure) at a ratio of more than 50% by mass relative to the total structural units. The content of structural units derived from a monomer having a nitrogen atom (preferably an amide group, more preferably a lactam structure) in the water-soluble polymer is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more. Particularly preferred is a homopolymer of a monomer having a nitrogen atom (preferably an amide group, more preferably a lactam structure) at 100% by mass.

[0058] Examples of monomers having a nitrogen atom (preferably an amide group, more preferably a lactam structure) include N-acryloylmorpholine, N-vinylpiperidine, N-vinylimidazole, N-vinylcarbazole, (meth)acrylamide; N-alkyl(meth)acrylamides such as N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, Nn-butyl(meth)acrylamide, N-sec-butyl(meth)acrylamide, and N-tert-butyl(meth)acrylamide; N,N-dialkyl(meth)acrylamides such as N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, N,N-di(n-butyl)(meth)acrylamide, and N,N-di(tert-butyl)(meth)acrylamide; N-hydroxymethyl(meth)acrylamide, N-hydroxyethyl ... N-hydroxyalkyl (meth)acrylamides such as acrylamide; N-vinyl carboxylic acid amides such as N-vinyl acetamide; N-hydroxyalkyl (meth)acrylamides such as N-(2-hydroxyethyl) (meth)acrylamide, N-(2-hydroxypropyl) (meth)acrylamide, N-(1-hydroxypropyl) (meth)acrylamide, N-(3-hydroxypropyl) (meth)acrylamide, N-(2-hydroxybutyl) (meth)acrylamide, N-(3-hydroxybutyl) (meth)acrylamide, and N-(4-hydroxybutyl) (meth)acrylamide; N-alkoxyalkyl (meth)acrylamides such as N-methoxymethyl (meth)acrylamide, N-methoxyethyl (meth)acrylamide, and N-butoxymethyl (meth)acrylamide; N,N-dimethylaminopropyl (meth)acrylamide, N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, and N-vinyl-2-caprolactam. Among these, taking into consideration the balance between protecting the surface of the object to be polished, improving the polishing rate of polysilicon, and reducing polishing residue, N-vinyl-2-pyrrolidone and N-acryloylmorpholine are preferred, and N-vinyl-2-pyrrolidone is more preferred.

[0059] These monomers having a nitrogen atom (preferably an amide group, more preferably a lactam structure) may be used alone or in combination of two or more kinds.

[0060] The monomer having a nitrogen atom (preferably an amide group, more preferably a lactam structure) may contain a structural unit derived from another copolymerizable monomer that is copolymerizable with the monomer, if necessary.

[0061] Examples of other copolymerizable monomers include carboxy group-containing monomers such as acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid; acid anhydride group-containing monomers such as maleic anhydride and itaconic anhydride; alkyl (meth)acrylate monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, t-butyl (meth)acrylate, n-propyl (meth)acrylate, n-hexyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; and (meth)acrylate monomers having an alicyclic structure such as cyclohexyl (meth)acrylate, cyclohexyloxyalkyl (meth)acrylate, t-butylcyclohexyloxyethyl (meth)acrylate, isobornyl (meth)acrylate, and dicyclopentanyl (meth)acrylate. monomers; (meth)acrylate monomers containing an alkoxy group or an oxyalkylene group, such as 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, methoxydiethylene glycol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, and polypropylene glycol mono(meth)acrylate; cyano group-containing monomers, such as acrylonitrile and methacrylonitrile; olefins, such as ethylene, propylene, butadiene, isoprene, and isobutylene; styrene, α-methylstyrene, vinyl acetate, vinyl propionate, vinyl stearate, alkyl vinyl ethers, vinyl toluene, vinyl pyridine, dialkyl itaconate esters, dialkyl fumarate esters, vinyl alcohol, allyl alcohol, methyl vinyl ketone, allyl trimethylammonium chloride, and dimethyl allyl vinyl ketone.

[0062] These other copolymerizable monomers may be used either individually or in combination of two or more.

[0063] Specific preferred examples of the water-soluble polymer having a nitrogen atom (preferably an amide group, more preferably a lactam structure) include poly N-vinylpyrrolidone (PVP) and polyvinylpyrrolidone-polyvinyl alcohol copolymer. Among them, poly N-vinylpyrrolidone (PVP) and polyvinylpyrrolidone-polyvinyl alcohol copolymer are preferred, and poly N-vinylpyrrolidone (PVP) is more preferred, taking into consideration the balance between protecting the surface of the object to be polished, improving the polishing speed of polysilicon, and reducing polishing residue.

[0064] The lower limit of the weight average molecular weight (Mw) of the water-soluble polymer is not particularly limited, but is preferably 1000 or more, more preferably more than 1000, even more preferably more than 1500, even more preferably more than 1500, particularly preferably 5000 or more, and most preferably more than 5000. The upper limit of the weight average molecular weight of the water-soluble polymer is not particularly limited, but is preferably 100,000 or less, more preferably less than 100,000, even more preferably less than 90,000, particularly preferably 80,000 or less, especially more preferably less than 80,000, and most preferably 55,000 or less. That is, the weight average molecular weight of the water-soluble polymer is preferably 1000 or more and 100000 or less, more preferably more than 1000 and less than 100000, even more preferably 1500 or more and 90000 or less, even more preferably more than 1500 and less than 90000, particularly preferably 5000 or more and 80000 or less, particularly more preferably more than 5000 and less than 80000, and most preferably more than 5000 and 55000 or less. If the water-soluble polymer has a weight average molecular weight in the above range, it has excellent solubility and can further improve the ratio (selectivity) of the polishing speed of polysilicon to the polishing speed of silicon nitride. In addition, if the water-soluble polymer has a weight average molecular weight in the above range, it can further improve the polishing speed of polysilicon.

[0065] The weight average molecular weight of the water-soluble polymer can be measured by gel permeation chromatography (GPC).

[0066] The content (concentration) of the water-soluble polymer is not particularly limited, but is preferably 0.0001% by mass or more, more preferably 0.0005% by mass or more, and even more preferably 0.001% by mass or more, based on the total mass of the polishing composition. The upper limit of the content of the water-soluble polymer is preferably 10% by mass or less, more preferably 1% by mass or less, and even more preferably 0.1% by mass or less, based on the total mass of the polishing composition. That is, the content of the water-soluble polymer is preferably 0.0001% by mass or more and 10% by mass or less, more preferably 0.0005% by mass or more and 1% by mass or less, and even more preferably 0.001% by mass or more and 0.1% by mass or less, based on the total mass of the polishing composition. If the content is within this range, the ratio (selectivity) of the polishing rate of polysilicon to the polishing rate of silicon nitride can be further improved while suppressing costs. If the content is within this range, the polishing rate of polysilicon can be further improved. In addition, if the polishing composition contains two or more water-soluble polymers, the content of the water-soluble polymers refers to the total amount of these.

[0067] [Dispersion medium] The polishing composition of the present invention preferably contains a dispersion medium for dispersing each component. Examples of the dispersion medium include water; alcohols such as methanol, ethanol, and ethylene glycol; ketones such as acetone, and mixtures thereof. Of these, water is preferred as the dispersion medium. That is, according to a more preferred embodiment of the present invention, the dispersion medium contains water. According to a further preferred embodiment of the present invention, the dispersion medium is substantially composed of water. Note that the above "substantially" means that a dispersion medium other than water may be included as long as the objective effect of the present invention can be achieved, and more specifically, the dispersion medium is preferably composed of 90% by mass or more and 100% by mass or less of water and 0% by mass or more and 10% by mass or less of a dispersion medium other than water, and more preferably composed of 99% by mass or more and 100% by mass or less of water and 0% by mass or more and 1% by mass or less of a dispersion medium other than water. As described above, more preferably, the dispersion medium is composed of only water.

[0068] From the viewpoint of not inhibiting the action of the components contained in the polishing composition, it is preferable for the dispersion medium to be water that contains as few impurities as possible. Specifically, pure water or ultrapure water from which impurity ions have been removed with an ion exchange resin and then foreign matter has been removed through a filter, or distilled water is more preferable.

[0069] [pH] The pH of the polishing composition of the present invention is not particularly limited, but is preferably 9.0 or more, more preferably 9.0 to 13.0, even more preferably 9.5 to 12.0, particularly preferably 10.0 to 11.5, and most preferably 10.5 to 11.5. If the pH is 9.0 or more, the polishing rate of polysilicon can be improved, and if the pH is 13.0 or less, the polishing rate of silicon nitride can be suppressed low. If the pH is within the above range, the ratio (selectivity) of the polishing rate of polysilicon to the polishing rate of silicon nitride can be sufficiently increased. The pH of the polishing composition is measured by the method described in the Examples below.

[0070] In the polishing composition of the present invention, ammonia and potassium compound also play a role as pH adjusters. If it is difficult to obtain a desired pH with these components alone, a pH adjuster may be added to adjust the pH within a range that does not impair the effects of the present invention.

[0071] The pH adjuster may be any of acids and bases other than ammonia and potassium compounds, and may be any of inorganic and organic compounds. The pH adjuster may be used alone or in combination of two or more kinds.

[0072] Specific examples of acids used as pH adjusters include inorganic acids such as sulfuric acid, nitric acid, boric acid, carbonic acid, hypophosphorous acid, phosphorous acid, and phosphoric acid; carboxylic acids such as formic acid, acetic acid, propionic acid, butyric acid, valeric acid, 2-methylbutyric acid, n-hexanoic acid, 3,3-dimethylbutyric acid, 2-ethylbutyric acid, 4-methylpentanoic acid, n-heptanoic acid, 2-methylhexanoic acid, n-octanoic acid, 2-ethylhexanoic acid, benzoic acid, glycolic acid, salicylic acid, glyceric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, maleic acid, phthalic acid, malic acid, tartaric acid, citric acid, and lactic acid; and organic acids such as organic sulfuric acids such as methanesulfonic acid, ethanesulfonic acid, and isethionic acid.

[0073] Specific examples of the base used as a pH adjuster include hydroxides or salts of Group 1 elements other than potassium, hydroxides or salts of Group 2 elements, quaternary ammonium hydroxide or its salt, etc. Specific examples of the salts include carbonates, hydrogen carbonates, sulfates, acetates, etc.

[0074] The amount of the pH adjuster added is not particularly limited, and may be appropriately adjusted so that the polishing composition has a desired pH.

[0075] [Electrical conductivity (EC) of polishing composition] The lower limit of the electrical conductivity (EC) of the polishing composition of the present invention is preferably 0.01 mS / cm or more, more preferably 0.1 mS / cm or more. The upper limit of the electrical conductivity (EC) of the polishing composition of the present invention is preferably 10 mS / cm or less, more preferably 3 mS / cm or less. Within the above range, the repulsion between the abrasive grains can be appropriately adjusted to ensure sufficient polishing speed and stability (especially for polysilicon). The electrical conductivity of the polishing composition can be adjusted by the amount of ammonia, the type and amount of potassium compound, the type and amount of pH adjuster, etc. The electrical conductivity of the polishing composition is measured by the method described in the Examples below.

[0076] [Other ingredients] The polishing composition of the present invention may further contain, as necessary, known additives that can be used in polishing compositions, such as surfactants, complexing agents, preservatives, and anti-fungal agents, to the extent that the effects of the present invention are not significantly impeded.

[0077] The polishing composition according to the present invention preferably does not substantially contain an oxidizing agent. If an oxidizing agent is contained in the polishing composition, the surface of the object to be polished (e.g., polysilicon) is oxidized to generate an oxide film, which may lengthen the polishing time. Specific examples of the oxidizing agent include hydrogen peroxide (H2O2), sodium persulfate, ammonium persulfate, and sodium dichloroisocyanurate. The polishing composition substantially does not contain an oxidizing agent means that the oxidizing agent is not intentionally contained at least. Therefore, a polishing composition that inevitably contains a small amount of an oxidizing agent due to raw materials, manufacturing method, etc. is included in the concept of a polishing composition that does not substantially contain an oxidizing agent. For example, the concentration of the oxidizing agent in the polishing composition is preferably 0.001% by mass or less, more preferably 0.0001% by mass or less, and even more preferably 0.00001% by mass or less (lower limit: 0% by mass).

[0078] [Method of manufacturing the polishing composition] The method for producing the polishing composition of the present invention is not particularly limited, and can be obtained, for example, by stirring and mixing abrasive grains, ammonia, a potassium compound, and, if necessary, a water-soluble polymer and other additives in a dispersion medium (e.g., water). Details of each component are as described above. In addition, ammonia is usually mixed with each component in the form of ammonia water, and the potassium compound is usually mixed with each component in the form of an aqueous potassium solution. Therefore, the present invention provides a method for producing a polishing composition, which includes a step of mixing abrasive grains, an aqueous ammonia solution, and an aqueous potassium compound solution.

[0079] The temperature at which the components are mixed is not particularly limited, but is preferably 10° C. to 40° C. Heating may be performed to increase the dissolution rate. The mixing time is also not particularly limited as long as the components can be mixed uniformly.

[0080] [Polishing method and semiconductor substrate manufacturing method] As described above, the polishing composition of the present invention is suitable for use in polishing an object to be polished that contains polysilicon and silicon nitride. Therefore, the present invention provides a polishing method for polishing an object to be polished that contains polysilicon and silicon nitride using the polishing composition.

[0081] The present invention further provides a method for producing a semiconductor substrate, the method comprising the polishing method, and a semiconductor substrate obtained by the method for producing a semiconductor substrate.

[0082] As a polishing device, a general polishing device can be used which is equipped with a holder for holding a substrate or the like having an object to be polished, a motor whose rotation speed can be changed, and a polishing platen onto which a polishing pad (polishing cloth) can be attached.

[0083] The polishing pad may be made of any material, including general nonwoven fabric, polyurethane, porous fluororesin, etc. It is preferable that the polishing pad has grooves formed thereon to allow the polishing liquid to accumulate.

[0084] Regarding the polishing conditions, for example, the rotation speed of the polishing platen was 10 rpm (0.17 s -1 ) or more 500rpm(8.3s -1 ) or less. The pressure (polishing pressure) applied to the substrate having the object to be polished is preferably 0.5 psi (3.4 kPa) or more and 10 psi (68.9 kPa) or less. The method of supplying the polishing composition to the polishing pad is not particularly limited, and for example, a method of continuously supplying the composition using a pump or the like is used. There is no limit to the amount of supply, but it is preferable that the surface of the polishing pad is always covered with the polishing composition of the present invention.

[0085] After polishing, the substrate is washed with running water, and water droplets adhering to the substrate are removed by a spin dryer or the like, followed by drying to obtain a substrate having a metal-containing layer.

[0086] The polishing composition of the present invention may be a one-liquid type or a multi-liquid type such as a two-liquid type. The polishing composition of the present invention may be prepared by diluting the stock solution of the polishing composition, for example, 10 times or more, with a diluent such as water.

[0087] (polishing speed) In an embodiment of the present invention, the polishing speed of polysilicon is preferably 2000 Å / min or more, more preferably 3000 Å / min or more, even more preferably 3100 Å / min or more, and particularly preferably 3200 Å / min or more. In an embodiment of the present invention, the polishing speed of silicon nitride is preferably 100 Å / min or less, more preferably 80 Å / min or less, even more preferably 50 Å / min or less, and particularly preferably 20 Å / min or less. (Selectivity) When the polishing composition of the present invention is used to polish an object containing polysilicon and silicon nitride, a high ratio of the polishing speed of polysilicon to the polishing speed of silicon nitride (high selectivity of polysilicon to silicon nitride) can be achieved. Specifically, in the embodiment of the present invention, the ratio (selectivity) of the polishing speed of polysilicon to the polishing speed of silicon nitride is preferably 10 or more, more preferably 20 or more, even more preferably 30 or more, even more preferably 70 or more, particularly preferably 100 or more, and most preferably 150 or more. The ratio (selectivity) of the polishing speed of polysilicon to the polishing speed of silicon nitride is preferably as high as possible, so there is no particular upper limit, but it is usually 300 or less, preferably 200 or less.

[0088] In this specification, the polishing rates of polysilicon and silicon nitride are calculated by the method described in the Examples. In this specification, the ratio (selectivity) of the polishing rate of polysilicon to the polishing rate of silicon nitride is calculated by the method described in the Examples. EXAMPLES

[0089] The present invention will be described in more detail with reference to the following examples and comparative examples. However, the technical scope of the present invention is not limited to the following examples. In addition, unless otherwise specified, "%" and "parts" mean "% by mass" and "parts by mass", respectively.

[0090] <Abrasive grain size> The average primary particle size of the abrasive grains was calculated from the specific surface area of ​​the abrasive grains measured by the BET method using a Micromeritics "Flow SorbII 2300" and the density of the abrasive grains. The average secondary particle size of the abrasive grains was measured using a Nikkiso Co., Ltd. dynamic light scattering particle size and particle size distribution analyzer UPA-UT151.

[0091] <Grain shape> The shape (external shape) of the abrasive grains was measured from images (magnification: 500k) taken using a scanning electron microscope (SEM) SU8000 (Hitachi High-Tech Corporation) by measuring the height and width of each protrusion present on 20 abrasive grains. The "average protrusion height" was then calculated by averaging the protrusion heights. The ratio of protrusion height to protrusion width was also calculated for each protrusion, and the average value was calculated.

[0092] <Silanol group density> The silanol group density per unit surface area of ​​the abrasive grain (unit: silanol group / nm 2 ) was calculated by the following method after each parameter was measured or calculated by the following measurement method or calculation method.

[0093] More specifically, C in the following formula is the total mass of the abrasive grains, and S in the following formula is the BET specific surface area of ​​the abrasive grains. More specifically, 1.50 g of abrasive grains as solid content is first collected in a 200 ml beaker, 100 ml of pure water is added to make a slurry, and then 30 g of sodium chloride is added and dissolved. Next, 1 N hydrochloric acid is added to adjust the pH of the slurry to about 3.0 to 3.5, and pure water is added until the slurry becomes 150 ml. The pH of this slurry is adjusted to 4.0 with a 0.1 N sodium hydroxide aqueous solution at 25°C using an automatic titration device (HIRANUMA SANGYO CO., LTD., COM-1700), and the volume V [L] of the 0.1 N sodium hydroxide aqueous solution required to increase the pH from 4.0 to 9.0 by pH titration is measured. The average silanol group density (pieces / nm 2 ) can be calculated using the following formula.

[0094]

number

[0095] In the above formula, ρ is the average silanol group density (pcs / nm 2 ) ; c represents the concentration (mol / L) of the aqueous sodium hydroxide solution used in the titration; V is the volume (L) of sodium hydroxide solution required to raise the pH from 4.0 to 9.0. ) ; N A represents the Avogadro constant (units / mol); C represents the total mass (solids) of the abrasive grains (g); S is the weighted average value of the BET specific surface area of ​​the abrasive grains (nm 2 / g).

[0096] <True density of abrasive grains (g / cm 3 )> True density of abrasive grains (g / cm 3) is measured by the following method. In detail, first, the abrasive water dispersion is placed in a crucible so that the solid content (abrasive grains) is about 15 g, and the moisture is evaporated at about 200 °C using a commercially available hot plate. Furthermore, in order to remove the moisture remaining in the voids of the abrasive grains, heat treatment is performed at 300 °C for 1 hour in an electric furnace (Advantec Toyo Co., Ltd., baking furnace), and the dried abrasive grains after the treatment are crushed in a mortar. Next, 10 g of the dried abrasive grains prepared above are placed in a 100 ml pycnometer (Wa (g)) whose weight has been measured in advance using a precision balance (A & D Co., Ltd., GH-202), and the weight is measured (Wb (g)). Then, 20 ml of ethanol is added, and the mixture is degassed for 30 minutes in a desiccator with reduced pressure. After that, the pycnometer is filled with ethanol, plugged, and the weight is measured (Wc (g)). After the weight of the abrasive grains has been measured, the contents of the pycnometer are discarded, and after cleaning, it is filled with ethanol and the weight is measured (Wd). From these weights and the temperature of the ethanol at the time of measurement (t (℃)), the true density is calculated using Equation 1 and Equation 2.

[0097]

number

[0098]

number

[0099] <pH of polishing composition> The pH of the polishing composition (liquid temperature: 25° C.) was measured with a pH meter (manufactured by Horiba, Ltd., model number: F-72 LAQUA (registered trademark)).

[0100] <Electrical Conductivity of Polishing Composition> The electrical conductivity (EC) of the polishing composition was measured with a tabletop electrical conductivity meter (manufactured by Horiba, Ltd., model number: DS-71 LAQUA (registered trademark)).

[0101] [Example 1] Colloidal silica as abrasive grains (average primary particle diameter: 30 nm, average secondary particle diameter: 60 nm, shape: confetti shape (average protrusion height: 5 nm, average "protrusion height / protrusion width" value: 0.3), silanol group density: 3.5 / nm 2 , true density: 2.05g / cm 3 ) at 3 mass%, as additive 1, 10 ppm of water-soluble polymer polyvinylpyrrolidone (PVP) (weight average molecular weight (Mw): 8000), as additive 2, 0.003 mass% ammonia water in terms of ammonia (NH3), as additive 2, 0.196 mass% potassium hydroxide aqueous solution in terms of potassium hydroxide (KOH) at 49 mass% in terms of potassium hydroxide (KOH) were added to pure water as a dispersion medium at room temperature (25°C) and then stirred and mixed for 30 minutes to obtain a polishing composition with a pH of 11. The electrical conductivity of the obtained polishing composition was measured and found to be 2.3 mS / cm.

[0102] [Examples 2 to 7, Comparative Examples 1 to 8] Polishing compositions of Examples 2 to 7 and Comparative Examples 1 to 8 were prepared in the same manner as in Example 1, except that the amount of abrasive grains, the type and amount of each of Additives 1 to 3, and the pH of the polishing composition were changed as shown in Table 1 below. The electrical conductivity of each of the obtained polishing compositions was measured, and the results are shown in Table 1 below. In Table 1 below, "-" indicates that the corresponding agent was not contained. In Comparative Example 6, tetramethylammonium hydroxide (TMAH) was used as Additive 2, and potassium carbonate (K2CO3) was used as Additive 3.

[0103] <Evaluation> The polishing rate, polishing residue and dishing when each polishing composition was used were evaluated by the following methods.

[0104] (Polishing equipment and polishing conditions) Polishing equipment: Applied Materials 200mm CMP single-sided polishing equipment Mirra (registered trademark) Polishing pad: Nitta DuPont hard polyurethane pad IC1010 Grinding pressure: 2psi (1psi=6894.76Pa) Polishing platen rotation speed: 103 rpm Head (carrier) rotation speed: 97 rpm Supply of polishing composition: free-flowing Polishing composition supply amount: 200mL / min Polishing time: 60 seconds.

[0105] (Object to be polished) The following three types of films were formed:

[0106] (1) A 5,000 Å thick polysilicon (Poly-Si) film is formed on the surface of a silicon wafer (200 mm, blanket wafer, manufactured by Advantec Corporation).

[0107] (2) A silicon wafer (200 mm, blanket wafer, manufactured by Advantec Corporation) with a 2000 Å-thick silicon nitride (SiN) film formed on the surface.

[0108] (3) An 8-inch Poly-Si pattern was formed on the surface of a silicon wafer (200 mm, blanket wafer, manufactured by Advantec Corporation). The Poly-Si pattern consists of the following three layers: The first layer is a plasma-deposited TEOS-SiO film with a thickness of 1,000 Å formed on a silicon wafer. The second layer is a 500 Å thick SiN film with a Sematech 854 pattern formed on top of the first layer. The third layer is a Poly-Si film with a thickness of 2,000 Å formed on the second layer. Fig. 2 is a cross-sectional view that shows a schematic representation of the object to be polished of (3) above. As shown in Fig. 2, the object to be polished 10 has three layers, a TEOS-SiO film 2, a patterned SiN film 3, and a Poly-Si film 4, laminated on a silicon wafer 1. In Fig. 2, H1 indicates the line width, and H2 indicates the space width. Also in Fig. 2, T1 indicates the thickness of the SiN film 3, and T2 indicates the thickness of the TEOS-SiO film 2 (the height from the surface of the TEOS-SiO film 2 to the surface of the SiN film 3 on the line of the SiN film 3).

[0109] [Polishing speed] Using each of the polishing compositions obtained above, the test wafers (1) and (2) were polished for 60 seconds under the above polishing conditions, respectively, and the polishing speed (polishing rate) was calculated by the following formula.

[0110]

number

[0111] The film thickness was measured using an optical film thickness measuring device (ASET-f5x: manufactured by KLA-Tencor Corporation), and the polishing speed (polishing rate) (Å / min) was evaluated by dividing the difference in film thickness before and after polishing by the polishing time. In Table 1 below, the polishing speeds for polysilicon and silicon nitride are shown in the "poly-Si" and "SiN" columns, respectively.

[0112] [Polishing residue] Using the polishing rate of polysilicon calculated by the above formula, The time required to polish the silicon nitride film was calculated, and the above (3) was polished. The thickness of the polysilicon remaining on the silicon nitride film of (3) after polishing was measured using an optical film thickness measuring device (ASET-f5x: manufactured by KLA Tencor). The film thickness at this point was regarded as the polishing residue, and was judged according to the following three-level judgment criteria. If it was △ or higher, it was acceptable for practical use.

[0113] Three-level evaluation criteria (Judgment): (Polishing remaining) ○: Less than 5 Å △: 5 Å or more and less than 15 Å ×: 15 Å or more [Dishing] Using each of the polishing compositions of Examples 1 to 7 and Comparative Examples 1 to 8, the test wafer of (3) above was polished under the above polishing conditions until the entire surface of the silicon nitride film was exposed. Then, the dishing amount (dishing depth) of the silicon nitride film and the polysilicon film was measured using an atomic force microscope (INSIGHT-CAP, manufactured by Bruker Japan) at the wiring width portion (H1 and H2 portions in FIG. 2) of 100 μm silicon nitride and 100 μm polysilicon, and judged according to the following four-level judgment criteria. If it is △ or higher, it is practically acceptable.

[0114] 4-level evaluation criteria (Judgment): (Amount of dishing) ◎: Less than 200 Å ○: 200 Å or more and less than 300 Å △: 300 Å or more and less than 400 Å × : 400 Å or more.

[0115] The evaluation results are shown in Table 1 below.

[0116] [Table 1]

[0117] As is clear from Table 1, it was found that the polishing compositions of Examples 1 to 7 can reduce both polishing residue and dishing compared to the polishing compositions of Comparative Examples 1 to 8. Among them, the polishing compositions of Examples 1 and 4 to 7 were particularly excellent in the effect of reducing polishing residue compared to other Examples. In particular, the polishing compositions of Examples 1, 5 and 6 were particularly excellent in the effect of reducing dishing. Furthermore, the polishing compositions of Examples 1 and 6 have a high selectivity (polishing rate of polysilicon / polishing rate of silicon nitride), and are therefore considered to be very suitable for use in polishing objects containing polysilicon and silicon nitride.

[0118] On the other hand, the polishing compositions of Comparative Examples 1 to 5 and 7 are examples in which the ammonia content is less than 0.002 mass%, or the potassium compound content is less than 0.004 mass% or more than 0.5 mass%, but they are not suitable for practical use because they leave a large amount of polishing residue.

[0119] The polishing composition of Comparative Example 6 has the same composition as the polishing composition of Comparative Example 6, except that no chelating agent was added in Example 10 described in JP 2015-70008 A. As can be seen from the results of Comparative Example 6, a quaternary ammonium salt such as tetramethylammonium hydroxide (TMAH) does not provide an effect of reducing polishing residue.

[0120] The polishing composition of Comparative Example 8 is an example in which the ammonia content exceeds 0.5 mass %, but is not suitable for practical use due to the large amount of dishing.

Claims

1. A polishing composition comprising an abrasive grain, ammonia, and at least one potassium compound selected from the group consisting of potassium hydroxide and a potassium salt, The content of the ammonia is 0.002 mass% or more and 0.5 mass% or less based on the total mass of the polishing composition, The content of the potassium compound is 0.004 mass % or more and 0.5 mass % or less relative to the total mass of the polishing composition.

2. The polishing composition according to claim 1 , further comprising a water-soluble polymer.

3. The polishing composition according to claim 2 , wherein the water-soluble polymer has a lactam structure.

4. The polishing composition according to any one of claims 1 to 3, having a pH of 9.0 or more.

5. 5. The polishing composition according to claim 1, wherein a ratio of the content of the potassium compound to the content of the ammonia (potassium compound / ammonia (mass ratio)) is 0.1 or more and 100 or less.

6. The silanol group density of the abrasive grains is 0 / nm 2 4 or more pieces / nm 2 The polishing composition according to any one of claims 1 to 5, wherein:

7. The polishing composition according to any one of claims 1 to 6, wherein the abrasive grains have a confetti-like shape.

8. The true density of the abrasive grains is 1.9 g / cm 3 The polishing composition according to any one of claims 1 to 7, wherein

9. A polishing method, comprising polishing an object containing polysilicon and silicon nitride with the polishing composition according to any one of claims 1 to 8.

10. A method for manufacturing a semiconductor substrate, comprising the method according to claim 9.

11. A semiconductor substrate obtained by the method for producing a semiconductor substrate according to claim 10.

Citation Information

Patent Citations

  • Polishing composition and polishing method

    CN112552824A

  • Chemical mechanical polishing slurry composition for polishing polycrystalline silicon film and method for producing same

    JP2009515335A

  • Chemical mechanical polishing aqueous dispersion, chemical mechanical polishing method using the same, and method of manufacturing chemical mechanical polishing aqueous dispersion

    JP2010161201A

  • Polishing composition and polishing method

    JP2015115360A

  • CMP polishing liquid and polishing method using the same

    JP2017178972A